Survismeter : fundamentals, concepts, and applications - Singh, Man; Singh, Sunita (Singapore : Pan Stanford, 2019)
This book presents the survismeter, a new invention that widely covers and determines PCPs of various molecules and experimentally measures the thermodynamic and kinetic stabilities of nanoemulsions. It unveils how a survismeter can measure surface tension, interfacial tension, wettability, viscosity, friccohesity, tentropy, rheology, density, activation energy, and particle size. It discusses novel models of molecular science that can be applied in the formulation and study of activities of functional molecules through their PCPs. It also introduces the new concept of friccohesity, which has emerged as an excellent substitute of viscosity and surface tension in experimental measurements as it does not require density measurements. It shows that the science and technology of the survismeter and friccohesity have become an inevitable part of scientific research, substantially integrating the domain of perfect industrial and academic formulations.
OCLC-licensed vendor bibliographic record.
Keywords: Liquids -- Measurement; TECHNOLOGY & ENGINEERING / Hydraulics; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Nuclear Physics; SCIENCE / Molecular Physics